Pengaruh Power Otot Tungkai, Kelentukan Otot Punggung Dan Koordinasi Mata Tangan Terhadap Kemampuan Smash Atlet Bolavoli Klub Mustank Kota Pekanbaru - Amin, Dwi Isniarti; Wahyuri, Asep Sujana; Irawan, Roma; Welis, Wilda; Ockta, Yovhandra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to determine how much influence leg muscle power, back muscle flexibility, and hand-eye coordination have on the smash ability of volleyball athletes. This research uses the Path Analysis method. The population of this study was 32 athletes, and the entire population was used as a sample. The final results show: The analysis results show that leg muscle power (X1) has a significant relationship and makes a significant contribution to smash ability. The research results show that back muscle flexibility (X2) has a significant relationship and contributes significantly to smash ability. The analysis results show that eye-hand coordination (X3) has a significant relationship and contributes significantly to smash ability. The results of the joint analysis (X1,2,3) show that leg muscle power, back muscle flexibility, and hand-eye coordination have a significant relationship and contribute significantly to smash ability. Results of multiple correlation analysis of 3 predictors with Fcount 9.33 > Ftable 2.88. This means a significant relationship exists between leg muscle power, back muscle flexibility, eye-hand coordination, and smash ability in volleyball athletes. In conclusion, there is a significant influence between leg muscle power, back muscle flexibility, and hand-eye coordination on the smash ability of volleyball athletes.. Keywords: Leg Muscle Strength, Back Muscle Flexion, Hand Eye Coordination, Smash Volleyball